Breaking the dormancy of rice seeds with various dormancy levels using steam and high temperature treatments in a steam nursery cabinet. (3rd April 2017) - Shiratsuchi, Hiroyuki; Ohdaira, Youichi; Yamaguchi, Hiromichi; Fukuda, Akari
Abstract: This study aimed to determine the appropriate steam treatment conditions, using a steam nursery cabinet, to break the dormancy of Japanese rice cultivar seeds exhibiting various dormancy levels. The influence of the temperature and duration of the steam treatments on the germination percentage and germination rate was investigated. In highly dormant 'Takanari' seeds, the steam treatment at 40 °C for 7 d increased the germination percentage and decreased the 50% germination time (T50S ; based on seed number); this treatment was as effective as the dry heat treatment at 50 °C for 7 d. For the medium dormant 'Moeminori' and 'Hitomebore' seeds, the steam treatment at 40 °C for 5 d decreased T50S sufficiently and more effectively than did the dry heat treatment at 50 °C for 7 d. For the slightly dormant 'Moeminori' seeds, the steam treatment at temperatures ranging from 24 °C to 40 °C for 7 d decreased T50S without a corresponding decrease in germination percentage to <90%. For the non-dormant 'Moeminori' and 'Takanari' seeds, the same steam treatments had no, or a little if any, useful effect on the germination percentage and T50S . Therefore, we concluded that, for the highly dormant seeds, steam treatment at 40 °C for 7 d was appropriate. Moreover, for less dormant seeds, steam treatment at 40 °C for 5 d was appropriate, and the steam treatment was not necessary for the non-dormant seeds.